Oxytetracycline residues in Thai pangas Pangasianodon hypophthalmus sampled from Sylhet sadar upazila, Bangladesh (Bangladesh Journal of Zoology, 2018)
Abstract not availableBangladesh J. Zool. 46(1): 81-86, 2018